Reversing motor adaptation deficits in the ageing brain using non‐invasive stimulation. (23rd June 2015) - Panouillères, Muriel T. N.; Joundi, Raed A.; Brittain, John‐Stuart; Jenkinson, Ned
Abstract : Key points: Healthy ageing in man is associated with a decline in motor adaptation. Transcranial direct current stimulation (TDCS) over the primary motor cortex (M1) or the lateral cerebellum can improve motor adaptation in young and older adults, but as yet no direct comparisons of TDCS effects exist between the two age groups and the two stimulation sites. TDCS over M1 enhanced the motor adaptation in both age groups by ∼30% relative to their respective non‐stimulated groups and improved the performance of older adults to the extent that it compared with that of young adults without stimulation. The study suggests that the plastic mechanisms activated by TDCS that underpin improvements in motor behaviour in young adults remain available in older adults. The results indicate that TDCS may be a useful tool to help combat the normal decline in motor performance seen in normal healthy ageing. Abstract: Healthy ageing is characterised by deterioration of motor performance. In normal circumstances motor adaptation corrects for movements' inaccuracies and as such, it is critical in maintaining optimal motor control. However, motor adaptation performance is also known to decline with age. Anodal transcranial direct current stimulation (TDCS) of the cerebellum and the primary motor cortex (M1) have been found to improve visuomotor adaptation in healthy young and older adults. However, no study has directly compared the effect of TDCS on motor adaptation between the two age populations. The aim of our study was to investigate whether the application of anodal TDCS over the lateral cerebellum and M1 affected motor adaptation in young and older adults similarly. Young and older participants performed a visuomotor rotation task and concurrently received TDCS over the left M1, the right cerebellum or received sham stimulation. Our results replicated the finding that older adults are impaired compared to the young adults in visuomotor adaptation. At the end of the adaptation session, older adults displayed a larger error (−17 deg) than the young adults (−10 deg). The stimulation of the lateral cerebellum did not change the adaptation in both age groups. In contrast, anodal TDCS over M1 improved initial adaptation in both age groups by around 30% compared to sham and this improvement lasted up to 40 min after the end of the stimulation. These results demonstrate that TDCS of M1 can enhance visuomotor adaptation, via mechanisms that remain available in the ageing population.